Oakland Suffrage March, 1908
Copy of photo of California suffragists marching in Oakland, August 27, 1908. From L-R: Lillian Harris Coffin, Mrs. Theodore Pinther, Jr., and Mrs. Theodore Pinther, Sr. Lillian Harris Coffin was the chief lobbyist for the California Woman Suffrage Association.